Elucidating the role of microbial factors and water stress in causing corky crack blemishes on potato tubers in South Africa - Van der Waals, Jacqueline Elise (University of Pretoria, 2024)
Dissertation (MSc (Plant Pathology))--University of Pretoria, 2020.